Electrodiagnostic Biomarkers in Paraneoplastic Retinopathy - Gougoulakis, Laura Sophie; Rothermundt, Christian; Flynn, Marie-Claire; Jörger, Markus; Todorova, Margarita G. (Klinische Monatsblätter für Augenheilkunde, 2024)
Objective Paraneoplastic retinopathy (PNR) is a rapid-onset photoreceptor and post-photoreceptor dysfunction triggered by a cross-reaction between antigens expressed by the underlying tumour and retinal proteins. The present study aims to determine the electrodiagnostic biomarkers that support the diagnosis of PNR and evaluate the effect of treatment.Methods A retrospective observational case-controlled study including 25 patients with suspected PNR, of which 11 patients were diagnosed with PNR. The presence of PNR was confirmed based on clinical examination, supported by colour fundus photography, fundus autofluorescence imaging, optical coherence tomography, fluorescein angiography, retinal vessel oximetry, colour test, full-field electroretinogram (ffERG), on-/off ERG, S-cone ERG, and multifocal ERG (mfERG). The relationships between the clinical symptomatology and the effect of therapy were evaluated.Results All PNR patients (Nr: 11) presented with subjective symptoms of newly reported central vision or visual field deterioration. Posterior segment findings showed a severe patchy-like retinal atrophy, attenuation of the retinal vessels, and a waxy optic disc. Optical coherence tomography revealed a discontinued ISe line, and multiple hyperreflective foci. Retinal vessel oxygen saturation was increased. Multifocal ERG revealed reduced central and paracentral responses and ffERG severely attenuated scotopic-, photopic-, on-/off- and S-cone responses. The colour vision test revealed a tritan-tetartan-weakness. Two of the PNR patients underwent rituximab therapy with no further progression and even recovery of electrodiagnostic responses.In 1 nPNR (non-paraneoplastic retinopathy) patient (total Nr: 14) pseudoxanthoma elasticum-related retinopathy was the reason for impaired vision. In 3 of 13 patients with bronchopulmonary cancer a MEK- and FGFR-inhibitor- drug toxicity was the reason for the visual deterioration.Conclusion Careful investigation for signs of central and/or peripheral visual field deterioration must be performed in the presence of history of a co-existing malignancy. The possibility of PNR should be taken into account. The electrodiagnostic biomarkers, suggested in this study, may help to promptly recognise PNR and also to evaluate the effect of implemented therapy.
Keywords: autoimmune retinal diseases; paraneoplastic retinopathy; subacute vision loss; photoreceptor dysfunction; therapy; electrodiagnostic biomarkers